Dose verification of volumetric-modulated arc therapy using one-dimensional and two-dimensional dosimeters. Issue 3 (19th November 2018) - Rehman, Jalil ur; Syed, Zahra; Hussain, Ghulam; Ahmad, Nisar; Asghar, H M Noor ul Huda Khan; Gilani, Zaheer Abbas; Nasar, Gulfam; Akhter, Malik M; Isa, Muhammad; Iqbal, Tahir
Abstract: Purpose: To verify dose delivery and quality assurance of volumetric-modulated arc therapy (VMAT) for head and neck (H&N) cancer. Method: The Imaging and Radiation Oncology Core Houston (IROC-H) H&N phantom with thermoluminescent dosimeters (TLDs) and films, were imaged with computed tomography scan and the reconstructed image was transferred to pinnacle treatment planning system (TPS). On TPS, the planning target volume (PTV), secondary target volume (STV) and organ at risk (OAR) were delineated manually and a treatment plan was made. The dose constraints were determined for the concerned organs according to IROC-H prescription. The treatment plan was optimised using adoptive convolution algorithm to improve dose homogeneity and conformity. The dose calculation was performed using C.C Convolution algorithm and a Varian True Beam linear accelerator was used to deliver the treatment plan to the H&N phantom. The delivered radiation dose to the phantom was measured through TLDs and GafChromic external beam radiotherapy 2 (EBT2) films. The dosimetric performance of the VMAT delivery was studied by analysing percent dose difference, isodose line profile and gamma analysis of the TPS-computed dose and linac-delivered doses. Result: The percent dose difference of 3.8% was observed between the planned and measured doses of TLDs and a 1.5-mm distance to agreement (DTA) was observed by comparing isodose line profiles. Passed the gamma criteria of 3%/3 mm was with good percentages. Conclusion: The dosimetric performance of VMAT delivery for a challenging H&N radiotherapy can be verified using TLDs and films embedded in an anthropomorphic H&N phantom.